Rethinking Standardization: the Social Meanings of Mycenaean Metal Cups. Issue 2 (25th January 2018) - Aulsebrook, Stephanie
Summary: Standardization can be conceptualized as a scale, from unique bespoke artefacts to uniform items produced on a factory line. It is usually analyzed in terms of whole objects, but is also applicable to their individual traits, such as shape, material, size, decoration or colour. Objects combining different levels of standardization across these traits are able to transmit more complex social meanings. Through the analysis of the standardization of their form and material, three metal cup types (shallow, stemmed and Vapheio) are singled out as having particular significance within elite Mycenaean culture. The combination of varying degrees of standardization in these vessels created gradients of value that expressed nuances of social identity whilst retaining their core message of high status. Differences in these combinations indicate that whilst shallow and Vapheio cups shared similar roles, the stemmed cup may have been intended to convey individuality within the elite community.